2021
DOI: 10.1093/infdis/jiab561
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vaccination Protects Against Severe Acute Respiratory Syndrome Coronavirus 2 in a Syrian Hamster Challenge Model

Abstract: Vaccines that are shelf stable and easy to administer are crucial to improve vaccine access and reduce SARS-CoV-2 transmission around the world. Here we demonstrate that an oral, adenovirus-based vaccine candidate protects against SARS-CoV-2 in a Syrian hamster challenge model. Hamsters administered two doses of VXA-CoV2-1 showed a reduction in weight loss and lung pathology and had completely eliminated infectious virus 5 days post challenge. Oral immunization induced anti-spike IgG and neutralizing antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…We observed robust anti-spike protein IgG responses after oral and IN r-Ad-S vaccination, as previously demonstrated in a different oral r-Ad-S hamster experiment ( 22 ). Further, we could detect elevated IgA in the serum and the BAL fluid of mucosally-immunized animals.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We observed robust anti-spike protein IgG responses after oral and IN r-Ad-S vaccination, as previously demonstrated in a different oral r-Ad-S hamster experiment ( 22 ). Further, we could detect elevated IgA in the serum and the BAL fluid of mucosally-immunized animals.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we show that oral and intranasal r-Ad-S vaccination decreased evidence of severe disease in vaccinated hamsters and reduced SARS-CoV-2 transmission to unvaccinated, naïve hamsters. We observed robust anti-spike protein IgG responses after oral and intranasal r-Ad-S vaccination, as previously demonstrated in a different oral r-Ad-S hamster experiment (22). Furthermore, we could detect elevated IgA in the serum and the BAL fluid of mucosally immunized animals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We propose an optimal SARS-CoV-2 infection dose for drug or vaccine efficacy studies in Golden Syrian hamsters of 10 2 TCID 50 , as this is sufficient to induce a reproducible (as confirmed by three independent experiments) weight loss, macroscopically visible lung affection, pneumonia, shedding of replication competent virus from 1 dpi, and the presence of high levels of replication competent virus in the respiratory tract on day 7 post infection, which will therefore allow a quantification of therapeutic effects. Infection doses of 10 5 TCID 50 that are generally used in Golden Syrian hamsters (Chan et al, 2020; Dowall et al, 2021; Francis et al, 2021; Johnson et al, 2022) may be too high to allow a disease progression at least partly resembling the distinctly slower processes in humans after a natural infection (Karimzadeh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…An oral tableted vaccine, the adenovirus-based VXA-CoV2-1/Vaxart, produced protection against SARS-CoV-2 in a Syrian hamster model in which the administration of two doses promoted a reduction in weight loss and lung pathology, and 5 days after injection, a complete deletion of the infectious virus was observed. Anti-spike IgG and neutralizing antibodies were induced upon oral immunization, with the serum demonstrating neutralizing activity [ 87 ]. Preliminary phase 1 trial results showed no severe adverse events and the triggering of multiple immune responses against SARS-CoV-2 antigens: a CD8 + cytotoxic T-cell response to the viral S protein that is necessary for long-lasting cross-reactive immunity, an increase in plasmablast cell numbers and an upregulation of the mucosal homing receptor, an increase in proinflammatory Th1 cytokines responsible for orchestrating the immune response to viral infection, and an IgA response in serum and/or nasal swab samples in 100% of the two-dose subjects [ 88 , 89 ].…”
Section: Vaccine Delivery: Future Prospectsmentioning
confidence: 99%